PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING - Muhammad Istifau Maulana; Sri Suryoko; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2016)
The research was motivated by of the many various alternative options for transportation services, especially land transportation. However, bus still be excellent for most of Indonesian people as a driving option.The purpose of this research is to determine the influence of service quality and price to customer loyalty, through customer satisfaction of PO. Nusantara’s customer. The population is all passengers direction Solo-Jakarta of PO. Nusantara. The sampling technique used was purposive sampling.the analysis used in this research is the path analysis using with SPSS Program 18.0, which previously tested the validity and reliability, coefisien  Corelation,coefisien determination, simple linear regression and multiple linear regression.The results showed that the quality of service and price partially or simultaneously affect customer satisfaction and loyalty. Variable price gives greater influence on customer satisfaction and loyalty of the variable quality of service.Suggestions can be submitted is that the PO. Nusantara can improve the quality of services provided, especially regarding punctuality and time left to place the goal. While in pricing, in addition to the cost element, the company also must pay attention to the price set by competitors.